COACHING AS AN INNOVATIVE TOOL FOR PREPARING INFORMATICS TEACHERS - Oshanova, Н.Т.; Nurbekova, Ғ.Б.; Salgozha, И.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article explores the possibilities of using coaching technology in the training of informatics teachers. It describes the main coaching tools and discusses the prospects of coaching as an innovative educational technology. A coach-trainer helps identify obstacles preventing future informatics teachers from achieving their goals and desired outcomes. They assist in defining steps to success using relevant coaching tools for a specific situation. The article analyzes the experience of coaching implementation in the education system of Kazakhstan. During the research, a survey was conducted among students based on their pedagogical practice results. The questionnaire analysis revealed that future informatics teachers lack confidence and encounter difficulties in their professional activities. The proposed approach to informatics teacher training using coaching technology aims to develop students' self-assurance, goal-setting and planning skills, student management abilities during lessons, and improvement of communication skills. All of these aspects can help future informatics teachers become more successful and confident in their professional endeavors.